2016
DOI: 10.5942/jawwa.2016.108.0005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Analysis of Disinfection Efficiency Through Computational Fluid Dynamics

Abstract: numerical approximations of model equations. His current research interests include sustainable water treatment system; computational fluid dynamics (CFD) applications to water and wastewater treatment, including ozone disinfection, digestion, and stabilization pond system; and integrated modeling framework of CFD and sustainability assessment models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…With Sc t = 1, [33] obtained after several simulations the best agreement with the experimental data and stressed that the turbulent Schmidt number has a significant impact on the numerical simulations of tracer transport. Kim et al [31] and Zhang et al [34][35][36] compared the results from numerical simulations based on the RANS with those obtained using LES. They found that in a tank where the flow field is far from ideal plug flow conditions, Sc t = 0.3 was needed to match with the LES data in the concentration RTD (Retention Time Distribution) curve, whereas for Sc t = 1, the numerical results overestimated the LES data.…”
Section: Water Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…With Sc t = 1, [33] obtained after several simulations the best agreement with the experimental data and stressed that the turbulent Schmidt number has a significant impact on the numerical simulations of tracer transport. Kim et al [31] and Zhang et al [34][35][36] compared the results from numerical simulations based on the RANS with those obtained using LES. They found that in a tank where the flow field is far from ideal plug flow conditions, Sc t = 0.3 was needed to match with the LES data in the concentration RTD (Retention Time Distribution) curve, whereas for Sc t = 1, the numerical results overestimated the LES data.…”
Section: Water Systemsmentioning
confidence: 99%
“…Arnold et al [22] Flow and tracer transport in open channels Exp − Sc t = 0.5-0.9 Djordjevic [23] Flow and tracer transport in open channels Exp/Num − Sc t = 1 Lin and Shiono [24] Flow and tracer transport in open channels Exp/Num − Sc t = 0.72 Simões and Wang [25] Flow and tracer transport in open channels Exp/Num − Sc t = 0.5 (horizontal), 1 (vertical) Gualtieri [30] Flow and tracer transport in a contact tank Exp/Num − Sc t = 1 Rauen et al [33] Flow and tracer transport in a contact tank Exp/Num − Sc t = 1 Kim et al [31] Flow and tracer transport in a contact tank Exp/Num − Sc t = 0.3 Zhang et al [34][35][36] Flow and tracer transport in a contact tank Exp/Num − Sc t = 0.7 Angeloudis et al [26][27][28][29] Flow and tracer transport in a contact tank Exp/Num − Sc t = 0.7 Martínez-Solano et al [32] Flow and tracer transport in a water tank Exp/Num − Sc t = 0.7 Oliver et al [37] Inclined negatively buoyant discharges Exp/Num − Sc t = 0.6 Graf and Cellino [41] Sediment-laden open channel flows Exp − Sc t > 1 (no bedforms), Sc t < 1 (bedforms) Hsu and Liu [42] Sediment-laden open channel flows Exp/Num − Sc t = 0.7 Amoudry et al [39] Sediment-laden open channel flows Exp/Num − Sc t = 0.7 (bed), Sc t = 0.52 (surface)…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al. performed simulations of Ozone contactor () and baffled contact tanks () using the Reynolds‐averaged Navier‐Stokes (RANS) equations. However, both these studies were for scaled models <11 m in the longest dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) presents the opposite end of the spectrum, producing flexible models with a large number of input parameters. Improvements in CFD modeling have enabled prediction of residence time indexes (e.g., t 10 / τ ) within approximately 10% (Zhang et al , Templeton et al ). While CFD has utility in estimating performance before reactors are constructed or modified, tracer tests provide greater accuracy for existing reactors at lower cost using more transparent methods.…”
mentioning
confidence: 99%